Differences in quality of life in patients with cutaneous lupus erythematosus with varying income levels. (May 2021) - Joseph, Adrienne; Prasad, Smriti; Hynan, Linda S.; Chren, Mary-Margaret; Chong, Benjamin
Background: Cutaneous lupus erythematosus (CLE) is an autoimmune photosensitive skin condition. The impact of income on quality of life has been incompletely characterized in CLE. Objectives: We aimed to assess how annual income affects quality of life among CLE patients. Methods: In this cross-sectional study of 238 patients with CLE, relationships between predictor variables including annual income and each SKINDEX-29 + 3 subdomain were identified using univariate and multivariable analyses. In addition, answers to individual SKINDEX-29 + 3 questions were compared across income groups. Clinical factors in patients making less than <10, 000 USD (N = 85) with worse SKINDEX-29 + 3 scores were also identified by univariate and multivariable analyses. Results: Patients making <10, 000 USD annually experienced worse quality of life across multiple SKINDEX-29 + 3 subdomains (p < 0.05). These patients specifically experienced poorer quality of life relating to social isolation and self-consciousness. (p < 0.001). Among those making <10, 000 USD, predictors for worse quality of life included females, smokers, and those with higher skin disease activity were identified (p < 0.05). Limitations: This is a single center study. Income was also self-reported and could not be verified. Conclusions: Lower income is related to poorer quality of life in patients with CLE. Specifically, patients experience limitations regarding social isolation and self-consciousness.